2014
DOI: 10.1111/pce.12337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated [CO2] on maize defence against mycotoxigenic Fusarium verticillioides

Abstract: Maize is by quantity the most important C4 cereal crop; however, future climate changes are expected to increase maize susceptibility to mycotoxigenic fungal pathogens and reduce productivity. While rising atmospheric [CO2] is a driving force behind the warmer temperatures and drought, which aggravate fungal disease and mycotoxin accumulation, our understanding of how elevated [CO2] will effect maize defences against such pathogens is limited. Here we report that elevated [CO2] increases maize susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 90 publications
6
86
0
Order By: Relevance
“…In any case, in other pathosystems, fungi have tended to be less affected by enhanced atmospheric [CO 2 ] than have the plant hosts (Chakraborty and Datta 2003). Vaughan et al (2014), for example, found that maize plants grown in elevated [CO 2 ] became more susceptible to Fusarium verticilioides, but the production of mycotoxins was unaffected by [CO 2 ].…”
Section: Discussionmentioning
confidence: 95%
“…In any case, in other pathosystems, fungi have tended to be less affected by enhanced atmospheric [CO 2 ] than have the plant hosts (Chakraborty and Datta 2003). Vaughan et al (2014), for example, found that maize plants grown in elevated [CO 2 ] became more susceptible to Fusarium verticilioides, but the production of mycotoxins was unaffected by [CO 2 ].…”
Section: Discussionmentioning
confidence: 95%
“…JA is also required for immunity against another common opportunistic soil-borne fungus, F. verticillioides , as the opr7opr8 mutants succumb to mesocotyl inoculation as rapidly as 8 h post-infection by this pathogen [76]. In another study, JA accumulation and JA biosynthetic gene induction correlated with increased resistance against F. verticillioides stalk rot in a CO 2 -dependent manner [148]. A recent genome-wide association study of maize infected by A. flavus identified the JA pathway as the most impacted between resistant and susceptible genotypes [149].…”
Section: Ja In Maize Pathogen and Nematode Defensementioning
confidence: 99%
“…As a consequence, the ISI-MIP protocol has been conducted with and without accounting for CO 2 -fertilization effects (further referred to as the CO 2 -ensemble and noCO 2 -ensemble, respectively). Recent findings also underline the importance of elevated temperatures and heat extremes (Gourdji et al, 2013;Deryng et al, 2014), ozone concentrations (Tai et al, 2014) as well as the potential of increasing susceptibility to disease as a consequence of elevated CO 2 levels (Vaughan et al, 2014) for agricultural yields, which may counteract potential yield gains by CO 2 -fertilization (Porter et al, 2014). Results for the CO 2 and noCO 2 -ensembles are presented separately, showing the range of potential manifestations and the additional risks of regional yield reductions, if effects of CO 2 -fertilization turn out to be lower than estimated by the model ensemble.…”
Section: Methods and Datamentioning
confidence: 99%